The Effect of Seasonal Employee Engagement on Performance at PG Tersana Baru (Journal of Business and Management, 2022)
Seasonal workers are will affect the sense of attachment of employees to the job or organization. This is very important for the organization and is a determining factor behind the high and low business performance. The lack of sense of attachment to employees PG TB can be a determining factor behind the low performance of seasonal employees. Employee engagement is the emotional commitment of employees to the organization according to goals to be achieved by the company. While performance is to arrange a goal that is useful for performance evaluation materials at the end of the period and for managing the work process during that period.This type research use quantitative methods. As for the method of sampling method, researchers used the snowball sampling method. The number of population is 372 and the number of sample is 79. These results of the research indicate that employee engagement in PG TB has a not positive relationship with employee performance, which is 25.7%. Based on the results of the study, the coefficient value of R Square (R2) is 0.066 or 6.6%, which means the other 93.4% is explained by other factors outside the performance attachment variable.Keywords: Seasonal employee, engagement and performance